A novel multi-species seed pelleting method to improve the efficiency of seed-based ecological restoration - Pedrini, Simone (Frontiers in Environmental Science, 2025)
Innovative and practical technological solutions are needed to support the restoration of degraded terrestrial ecosystems. Seed coating technology applied to native species is a promising solution to improve the efficiency of seed-based ecological restoration. Seed pelleting is a type of seed coating that increases the size and standardises the shape of small seeds, facilitating precision seeding. Such technology has been tested on native species, but in previous studies, the pelleting process was performed with one species at a time (Single Species Pelleting, SSP). Although effective, such an approach might be too costly when applied to the many species required to restore highly diverse ecosystems. Here, we present a novel method for seed pelleting multiple small-seeded species (MSP) in a single pass. Seeds of different species are mixed and then sorted by size through a series of sieves. The pelleting process starts with the smallest seeds. When the pellet reaches the size of the second-smallest seeds, those are added to the mix until they all reach the size of the third-smallest seeds. The process is repeated until all seeds are added and all pellets reach a uniform target size. To assess the efficacy of this new method, the time required to perform the pelleting and the associated cost on two batches of 13 and 19 species were compared to the SSP. The MSP allowed for pelleting times 5.6 to 10.2 times faster and a 3.1 to 3.9-fold reduction in cost compared to the SSP approach. The MSP approach is an effective method for increasing the efficiency of seed pelleting on diverse restoration mixes. Ultimately, the MSP technology combined with broad-acre seeding agricultural equipment has the potential to drastically increase the scale and effectiveness of seed-based restoration of degraded terrestrial ecosystems.